2021
DOI: 10.3390/w13162165
|View full text |Cite
|
Sign up to set email alerts
|

Closing Water Cycles in the Built Environment through Nature-Based Solutions: The Contribution of Vertical Greening Systems and Green Roofs

Abstract: Water in the city is typically exploited in a linear process, in which most of it is polluted, treated, and discharged; during this process, valuable nutrients are lost in the treatment process instead of being cycled back and used in urban agriculture or green space. The purpose of this paper is to advance a new paradigm to close water cycles in cities via the implementation of nature-based solutions units (NBS_u), with a particular focus on building greening elements, such as green roofs (GRs) and vertical g… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
21
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
4
2

Relationship

1
5

Authors

Journals

citations
Cited by 39 publications
(29 citation statements)
references
References 121 publications
(183 reference statements)
0
21
0
Order By: Relevance
“…Within the COST Action Circular City, the NBS units and interventions (NBS_u/i) were analyzed under the perspectives of four selected urban sectors, which refer to the different fields of activities for circular management of resources in cities, namely, the built environment [14], urban water management [15], resource recovery [16], and urban farming [17]. With circularity always in focus, each sector first identified the most relevant UCCs being dealt with and then the most applicable NBS_u/i to address the relevant UCCs.…”
Section: Nature-based Solution Concept Under the Perspective Of Different Urban Sectorsmentioning
confidence: 99%
See 4 more Smart Citations
“…Within the COST Action Circular City, the NBS units and interventions (NBS_u/i) were analyzed under the perspectives of four selected urban sectors, which refer to the different fields of activities for circular management of resources in cities, namely, the built environment [14], urban water management [15], resource recovery [16], and urban farming [17]. With circularity always in focus, each sector first identified the most relevant UCCs being dealt with and then the most applicable NBS_u/i to address the relevant UCCs.…”
Section: Nature-based Solution Concept Under the Perspective Of Different Urban Sectorsmentioning
confidence: 99%
“…• Built environment: Pearlmutter et al [14] focused on building systems and identified the "wicked problem of water"; more provision of services by NBSs requires a higher water use, which is commonly solved by importing water from outside the city. The authors proposed to challenge this conundrum by focusing on those NBS_u/i classified as vertical greening systems and green roofs [13], and how they can be used to foster graywater reuse and capture available rainwater.…”
Section: Nature-based Solutions Units and Interventions And Supporting Units Under The Perspective Of Different Urban Sectorsmentioning
confidence: 99%
See 3 more Smart Citations